Assessment of Client's Satisfaction with Quality of Antenatal Care at Korle-Bu Teaching Hospital - Freeman, F.B (University of Ghana, 2015)
Quality of service at the antenatal clinic is a key success factor in healthcare delivery in hospitals in Ghana. So, the assessment of clients‟ level of satisfaction with quality antenatal care is crucial upon which improvement of health service delivery can be undertaken periodically. Thus, the aim of this study was to assess the satisfaction of clients with the quality of antenatal care at Korle – Bu teaching hospital.
Keywords: ASSESSMENT; CLIENTS’ SATISFACTION; QUALITY; ANTENATAL CARE; KORLE – BU TEACHING HOSPITAL